2017
DOI: 10.1186/s40337-017-0156-0
|View full text |Cite
|
Sign up to set email alerts
|

Relational containment: exploring the effect of family-based treatment for anorexia on familial relationships

Abstract: BackgroundThe aim of this research was to investigate the process of familial relationship change for adolescents with anorexia nervosa and their parents, who participated in Family-Based Treatment (FBT).MethodA Constructionist grounded theory design was employed with purposive sampling. Sixteen young people between 12 and 18 years with a good outcome in FBT and twenty-eight of their parents participated. Young people and their parents took part in separate interviews at the end of treatment. Each interview wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 54 publications
4
53
0
5
Order By: Relevance
“…In previous research, we have shown that greater attendance by fathers predicts better patient outcomes (Hughes, Burton, Le Grange, & Sawyer, ). This may be in part due to fathers' involvement contributing to greater relational containment whereby treatment enhances parental confidence and the parent–child relationship, leading the adolescent to feel more secure and to engage more readily in the therapeutic process (Wallis et al, ). Taken together, the results suggest that the father's relationships with their child and the therapist, as well as his participation in treatment, can have a significant impact on treatment progress.…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, we have shown that greater attendance by fathers predicts better patient outcomes (Hughes, Burton, Le Grange, & Sawyer, ). This may be in part due to fathers' involvement contributing to greater relational containment whereby treatment enhances parental confidence and the parent–child relationship, leading the adolescent to feel more secure and to engage more readily in the therapeutic process (Wallis et al, ). Taken together, the results suggest that the father's relationships with their child and the therapist, as well as his participation in treatment, can have a significant impact on treatment progress.…”
Section: Discussionmentioning
confidence: 99%
“…Family therapies, such as the family‐based therapy or the Maudsley family therapy (Le Grange & Eisler, ; Murray & Le Grange, ), have their roots in the systemic approach (Minuchin et al, ; Selvini Palazzoli, ) along with the behavioural one; they have shown high levels of efficacy in the treatment of anorexia nervosa and in particular of adolescents (Couturier, Kimber, & Szatmari, ; Fisher, Hetrick, & Rushford, ). Early studies (Wallis, Rhodes, et al, ) investigating the therapeutic process and the changing mechanisms in family‐based therapy showed that relational containment and parental confidence may play a pivotal role in enhancing the adolescent physiological individuation and autonomy process. Moreover, there is preliminary evidence that supports also therapeutic methods coming from different theoretical approaches, such as the systemic family therapy (Agras et al, ) or the dynamic family therapy of the Montsuris (Paris)‐based group (Godart et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, we can see that uniting the parents in managing the re‐feeding can provide ‘relational containment,’ and when that is achieved the parents are available to help the young person regulate their distress, as Wallis et al. () describe. Initially that distress arises in relation to eating, weight, and shape issues.…”
Section: Discussionmentioning
confidence: 99%
“…Wallis et al. () report a qualitative study of changes in family relationships resulting from FBT. They drew their observations from interviews with members of 33 families successfully treated (emphasis added).…”
mentioning
confidence: 99%
See 1 more Smart Citation